Dimethyl Sulfoxide (DMSO) has an Additive Effect and Alters Minimal Inhibitory Concentrations of Antifungal Drugs - Mohammad Akram Randhawa, Mohammad Akram Randhawa; Salih Hamad Mohamad Aljabre*, Salih Hamad Mohamad Aljabre* (Journal of Rawalpindi Medical College, 2007)
Background: Dimethyl sulfoxide (DMSO) is commonly used as a solvent for anti-fungal drugs. It has been reported to possess anti-fungal activity by itself so may interfere in the evaluation and comparison of antifungal drugs. DMSO 1% and below are usually considered to possess insignificant effect on the growth of fungi. The present study was aimed to determine any additive/synergistic effect of DMSO (1%) with anti-fungal drugs. Methods: The effect of DMSO (1%) was determined on the colonial growth of Trichophyton rubrum, and Microsporum canis along with clotrimazole, griseofulvin, ketoconazole and thymoquinone (an active principle of Nigella sativa). Similarly, the ability of DMSO (1%) to enhance the effect of amphotericin-B and thymoquinone was observed on the growth of Aspergillus niger. The fungi were grown in three sets of plates of dermasel agar for each drug containing: (a) serial dilutions of the drug alone; (b) serial dilutions of the drug plus DMSO 1% in each dilution and (c) dermasel agar alone, as control. Results: DMSO (1%) lowered the MICs of all drugs tested against the fungi used, except amphotericin-B against Aspergillus niger. Presence of DMSO (1%) in serial dilutions of drugs also significantly shifted the growth curves of fungi towards right. Conclusion: DMSO, as a solvent, is one of the important factors that can alter the results of antifungal drugs.